Tick masquerading as skin tag − A rare case report - Seethalakshmi Ganga Vellaisamy; Navakumar Manickam; Anbulenin Kulandaivel; Kannan Gopalan (Wolters Kluwer Medknow Publications, 2022)
We report the case of a 16-year-old boy who presented with a painful skin lesion over the left lower eye lid following a history of travel to forest which masqueraded as skin tag. Excision biopsy showed features suggestive of hard tick. We report this unusual case of tick bite mainly to stress the importance of proper clinical evaluation, appropriate treatment like limited surgical excision, regular follow-up in view of prevention of potential disease transmission by the tick. Timely detection and treatment of tick bite is important to prevent multisystem complication that may develop later in life.